Navigating the Fiscal Challenges Ahead. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2010)
With increasing fiscal challenges in the aftermath of the global financial crisis, multilateral surveillance of fiscal developments, a key part of the IMF's surveillance responsibilities, has gained further importance. In response, the Fiscal Monitor was launched in 2009 to survey and analyze the latest public finance developments, update fiscal implications of the crisis and medium-term fiscal projections, and assess policies to put public finances on a sustainable footing. Previous issues of the Monitor were published in the IMF's Staff Position Notes series, but starting with this issue, the Monitor will be a part of the IMF's World Economic and Financial Surveys series, to complement the overviews presented in the World Economic Outlook (WEO) and the Global Financial Stability Report (GFSR). The Fiscal Monitor is prepared twice a year by the IMF's Fiscal Affairs Department. The Monitor's projections are based on the same database used for the April 2010 WEO and GFSR. The fiscal projections for individual countries have been prepared by IMF desk economists, and, in line with the WEO guidelines, assume that announced policies will be implemented.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet